Predictors of suicide in adolescents and adults with mood and common comorbid disorders. (February 2014) - Barzilay, Shira; Apter, Alan
SUMMARY Depression is the most common disorder in people who die by suicide. Studies have recognized many risk factors for suicide in mood disorders. However, there are inconsistencies in findings supporting the independent and predictive contribution of these factors. The aim of this review is to underline the most established and recent research findings on suicide risk factors in individuals with mood and common comorbid disorders. The clinical predictors with the most support are a past history of suicidal behavior, recurrent depression and mood instability. Comorbid psychiatric disorders, particularly substance or alcohol abuse and borderline personality disorder, are also associated with increased risk. Important psychosocial risk factors are family history of suicidal behavior and impulsive aggression. Other risk factors showed limited or contradictory findings. A comprehensive exploration of suicide risk factors in people with mood and comorbid disorders may help clinicians to identify patients at high suicide risk and improve suicide prevention efforts.